Evaluation of Synergetic Activity of Honey and Ginger Extracts on Pseudomonas aeruginosa and Methicillin-Resistant Staphylococcus aureus - Idris, U. A.; Tijjani, M. B.; Aliyu, M. S. (UMYU Journal of Microbiology Research)
This study was conducted to determine the antimicrobial and synergistic activity of honey and ginger extracts on Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus (MRSA).Agar well diffusion method was used to determine susceptibility of the test organisms using honey and ginger extracts individually, and the Minimum Inhibitory Concentrations of the antimicrobial agents was measured using the tube dilution method. Different proportions of 10% v/v concentrations of the antimicrobials were mixed and their activity against the test organisms determined also using the agar diffusion method. The most active proportion was taken as the proportion with the widest diameter zone of inhibition. The MIC and MBC of the most active proportions on the different test organisms were then determined. Honey-ginger powder extract mixtures produced the highest inhibition compared to the use of honey or ginger extract individually. The zones of inhibitions produced by a mixture of ginger extract and honey each of 10%v/v concentration on both Pseudomonas aeruginosa and MRSA was higher than zones of inhibition by honey and ginger extract of the same concentration used individually. Minimum inhibitory concentration (MIC) of the most active proportions of honey-ginger extract mixtures on both Pseudomonas aeruginosa and MRSA was 1.25% v/v while minimum bactericidal concentrations (MBCs) of the different most active proportions were 2.5% v/v for both of the test organisms.